Physiological adaptations following a four-week of high-intensity functional training - Kliszczewicz, Brian; McKenzie, Michael; Nickerson, Brett (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. High-Intensity Functional Training (HIFT) is a popular mixed-modal program that utilizes both resistance and aerobic based exercises. The aim of this study was to examine the physiological effects of the HIFT programing on physically active men (10) and women (10) over a four-week period through the measure of the aerobic capacity, anaerobic capacity, and maximal weight lifted. Methods. The participants first completed a maximal oxygen consumption (VO2max) test. After 48-hours of rest, the subjects completed the anaerobic capacity test via the Wingate protocol. Following the Wingate test, the subjects performed a 1-repetition maximum test for squat, snatch and clean at the offsite training location. After the pre-measurements were obtained, the subjects entered a four-week the HIFT intervention and returned to the lab for all post-measurements. Results. Significant improvements were observed in male and female: VO2 max (Pre: 46.7 ± 2.6, 33.7 ± 1.7 mL/kg/min; Post: 49.0 ± 3.0, 35.0 ± 1.8 mL/kg/min), Peak Wingate Power (Pre: 1206 ± 106, 708 ± 44 W; Post: 1283 ± 88, 809 ± 38 W) Mean Wingate Power (Pre: 680 ± 46, 704 ± 48 W; Post: 434 ± 15, 458 ± 18 W; p < 0.05), back squat (Pre: 128.8 ± 8.8 kg, 44.1 ± 6.8 kg; Post: 142.7 ± 9.8, 54.3 ± 6.2 kg) clean (Pre: 82.5 ± 6.2, 24.1 ± 3.4 kg; Post: 92.7 ± 5.8, 33.2 ± 3.3 kg) and snatch (Pre: 59.3 ± 4.4, 20.9 ± 1.7 kg; Post: 69.1 ± 5.3, 25.0 ± 2.3 kg; p < 0.05), respectively. No gender influence on interaction was observed over time (p > 0.05). Conclusion. The HIFT demonstrated the rapid physiological improvements in strength, aerobic and the anaerobic capacity following a four-week intervention in the physically active participants.